Penerapan Aspek Bioetik Kultur Jaringan Terhadap Permasalahan Kontaminasi Mikroorganisme Di Salah Satu Laboratorium Kultur Jaringan Kota Medan - Mega Utami; Alfina Siska Dewi; Waliid Naufal; Shafwan Pulungan, Ahmad; Situmorang, Nurbaity (Fakultas Pertanian, Program Studi Agroteknologi, 2025)
Abstract Contamination of microorganisms, especially fungi and bacteria, is a major challenge in the success of tissue culture, which can come from unsterilized explants, tools, or work environment. The application of bioethical principles, such as strict sterilization and sustainable practices, is expected to reduce the risk of contamination. This study aims to analyze the application of bioethics in tissue culture and identify factors causing contamination in tissue culture laboratories in Medan City. The research method used a descriptive qualitative approach with data collection through literature study, interviews, and questionnaires to 14 respondents. The results showed that most respondents understood the principles of bioethics and had implemented sterilization procedures well. However, guidance on contamination prevention was lacking, and the effectiveness of bioethics implementation in reducing contamination varied. Periodic evaluation of the success of tissue culture has been conducted, but limited facilities and external factors are still an obstacle. The conclusions of this study emphasize the importance of improved bioethics training, provision of adequate facilities, as well as the use of new technologies and inter-institutional collaboration to reduce the risk of microorganism contamination in tissue culture. Keyword: Tissue culture, microorganism contamination, bioethics Abstrak Kontaminasi mikroorganisme terutama jamur dan bakteri menjadi tantangan utama dalam keberhasilan kultur jaringan yang dapat berasal dari eksplan, alat, atau lingkungan kerja yang tidak steril. Penerapan prinsip bioetika, seperti sterilisasi ketat dan praktik berkelanjutan, diharapkan dapat mengurangi risiko kontaminasi. Penelitian ini bertujuan menganalisis penerapan bioetika dalam kultur jaringan dan mengidentifikasi faktor penyebab kontaminasi di laboratorium kultur jaringan di Kota Medan. Metode penelitian menggunakan pendekatan deskriptif kualitatif dengan pengumpulan data melalui studi pustaka, wawancara, dan kuesioner terhadap 14 responden. Hasil penelitian menunjukkan bahwa sebagian besar responden memahami prinsip bioetika dan telah menerapkan prosedur sterilisasi dengan baik. Namun, panduan pencegahan kontaminasi masih kurang, dan efektivitas penerapan bioetika dalam mengurangi kontaminasi bervariasi. Evaluasi berkala terhadap keberhasilan kultur jaringan telah dilakukan, tetapi keterbatasan fasilitas dan faktor eksternal masih menjadi kendala. Kesimpulan penelitian ini menekankan pentingnya peningkatan pelatihan bioetika, penyediaan fasilitas yang memadai, serta penggunaan teknologi baru dan kolaborasi antar lembaga untuk mengurangi risiko kontaminasi mikroorganisme dalam kultur jaringan. Kata Kunci: Kultur jaringan, kontaminasi mikroorganisme, bioetika